Blood Coagulation Factor X Deficiency Causes Partial Embryonic Lethality and Fatal Neonatal Bleeding in Mice - Dewerchin, Mieke; Liang, Zhong; Moons, Lieve; Carmeliet, Peter; Castellino, Francis J.; Collen, Désiré; Rosen, Elliot D. (Thrombosis and Haemostasis, 2000)
Mice with a total deficiency in blood coagulation Factor X (FX) were generated by targeted replacement of an 18-kb fragment of the FX gene, comprising all exons encoding the mature FX protein, with a neor cassette. The genotype distribution among the offspring from heterozygous breeding pairs suggested that FX deficiency resulted in partial embryonic lethality, with approximately one-third of the FX−/− embryos dying around embryonic day (E) 11.5-12.5. Two of 44 non-resorbed FX−/− embryos analyzed at these stages showed signs of massive bleeding, one of which into the brain ventricles, but no histological defects in the vasculature of these embryos or their yolk sac were observed. The remainder of the FX−/− embryos appeared normal and survived to term, but the majority of neonates (90%) died within 5 days, most frequently from intraabdominal bleeding. The remaining FX−/− animals succumbed between postnatal day (P)5 and P20 with intraabdominal, subcutaneous, or intracranial bleeding or a combination thereof. The lethal phenotype of the FX−/− mice illustrates the importance of FX function in embryonic and postnatal survival and demonstrates that these mice serve as effective models of the bleeding disorders observed in severe FX deficiency in humans.
Keywords: Factor X; embryonic development; neonatal bleeding; gene deletion; coagulation